PERANCANGAN APLIKASI PEMBELAJARAN BAHASA ASING YANG INTERAKTIF MENGGUNAKAN METODE MERN - Faris Mas’ud; Nuryuliani Nuryuliani (Jurnal Ilmiah Teknik, 2024)
There are many ways to learn some foreign language. Some people are afraid to learn a foreign language because they are afraid of the high costs. This can be solved by using a website-based online chat application, which provides features for practicing foreign language conversations. The "Website-based Online Chat" application applies MERN stack technology (MongoDB, Express JS, React JS, Node JS). The design of this application aims to provide an interactive and effective foreign language learning experience. The "Online Chat" application allows users to interact directly via the chat feature in real time. The output of this research is a website-based Online Chat Application Prototype developed with MERN technology, which consists of components such as Mongo DB, Express JS, React, and Node JS. This application provides a feature for communicating via Online Chat in real time so that communication can be more efficient and ontime.